CALM for moms : worry less in four simple steps - Marek, Denise, 1969- (Familius, 2022)
"Motherhood is stressful, but international award-winning speaker and worry management expert Denise Marek is here to tell you that you can stress less by learning to worry wisely! With her proven CALM method, a four-step process that has helped many individuals and organizations around the world connect with their inner peace, overcome their fears, and take the risks that are essential for success, mothers can tackle the stress of parenting. Whether you suffer from chronic worry about finances, family difficulties, your children's happiness, or even your teen getting home late, the CALM process can teach you how to handle it all."--Amazon.com.